Rice sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
This Executive Brief analyses the main trends of the world rice market in 2012-13. Compared to other cereal markets, rice prices were exceptionally stable in 2012, though they continued at a high level. They remained vulnerable to public policy measures in major producing countries (e.g. India, Thailand and China), and ACP producers, who still depend on imports to meet much of their rice demand, have little influence on prices. The Brief presents developments of the rice sector, both in the EU and the ACP countries, where a series of political measures have been taken to promote local rice production. Finally, it highlights a number of challenges for ACP countries to reconcile the promotion of increased national production with the need to meet rising consumer demand.